Muon spectroscopy of a 12-phosphatetraphene with extremely efficient radical trapping properties - Shigekazu Ito; Kohei Yasuda; Keisuke Ishihara; Victoria L. Karner; Kenji M. Kojima; Iain McKenzie (Scientific Reports)
Abstract This paper describes muon spin spectroscopy studies of 12-phosphatetraphene stabilized by a peri-trifluoromethyl group and a meso-aryl substituent. Even though the prepared solution in tetrahydrofuran (THF) was quite dilute (0.060 M) for transverse-field muon spin rotation (TF-µSR) measurements, the π-extended heavier congener of tetraphene presented a pair of signals due to a muoniated radical from which the muon hyperfine coupling constant (hfc) was determined. This muoniated radical was produced by the diffusion-controlled regioselective addition of muonium (Mu = [µ+e–]) to the sp2-hybridized phosphorus atom. The assignment of the muoniated radical structure was confirmed by observing a resonance due to the I = 1/2 (31P) nucleus in a muon (avoided) level-crossing resonance (µLCR) spectrum. The 31P hfc was determined from the resonance position, and a comparison with the value obtained from density functional theory (DFT) calculations indicated that the radical retained a flat π-delocalized tetracyclic skeleton. This higher energy structure is hypothesized to be preferable because of the increased zero-point energy of the light mass of the muon. The findings of this study could be fruitful in developing novel spin-functional materials featuring efficient radical capture and π-delocalized paramagnetic molecular systems.